Compensation and Span of Control in Hierarchical Organizations - Ortín‐Ángel, Pedro; Salas‐Fumás, Vicente (Journal of Labor Economics, 2002)
This article presents evidence on the relationship between compensation ratios and spans of control within hierarchical organizations. We find that compensation ratios are lower than span of control at any position within the hierarchy, which is consistent with an elasticity of compensation to a number of subordinates lower than one. Managers’ human capital endowments determine a significant part of the salary differences throughout hierarchical levels, as predicted by models of talent allocation in hierarchies. Differences in the size of firms should be attributed more to differences in their number of hierarchical levels than to variations in the span of control.